Desorption isotherms of flaxseeds (Linum usitatissimum L.) and thermodynamic parameters of the process - Valente, Maria da Conceição; Nascimentro, Rafael; Santana, Elza; Faria, Lênio José; Costa, Cristiane Maria (Revista Ciência Agronômica, 2020)
Sorption isotherms of flaxseeds were determined by static gravimetric method at temperatures 40, 60, and 80 ºC, over a relative moisture range of 10-95%. Six mathematical models were applied to analyze the experimental data. The modified GAB model showed the best fitting to the experimental data. The isosteric heat and differential entropy were determined by applying the Clausius-Clapeyron and Gibbs-Helmholtz equations, respectively. The isosteric heat and the entropy of desorption isotherm presented similar behavior, with a sharp change of 10% in the equilibrium moisture content. The enthalpy–entropy compensation theory was applied to the isotherms, indicating that they are enthalpy-controlled.